Multilayer composite encapsulation material and preparation method thereof, flexible OLED display screen

By combining functionalized polyacrylate copolymer emulsion with nano-silica materials and using a multilayer alternating structure, the problem of water and oxygen erosion in flexible OLED displays has been solved, resulting in a high-barrier and mechanically reliable encapsulation material suitable for high-end flexible OLED displays.

CN122641185APending Publication Date: 2026-08-25HUNAN BINFEILIHE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610796310.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-04
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

The organic light-emitting materials of flexible OLED displays are easily corroded by moisture and oxygen. Existing encapsulation materials have insufficient barrier properties, weak interfacial bonding, and damage to devices during high-temperature processes, making it difficult to meet the requirements of ultra-high barrier properties and mechanical reliability.

Method used

Functionalized polyacrylate copolymer emulsion is combined with nano-silica material to form chemical bonds through in-situ polymerization, constructing a multi-layer organic-inorganic alternating structure. Combined with slot coating and atomic layer deposition processes, a dense and tough multi-layer encapsulation material is formed.

Benefits of technology

It achieves ultra-low water and oxygen permeability (below 1.0×10-6 g/m2·day), while possessing excellent flexibility and reliable interface bonding, meeting the long lifespan requirements of high-end flexible OLED displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122641185A_ABST
    Figure CN122641185A_ABST
Patent Text Reader

Abstract

This invention discloses a multilayer composite encapsulation material and its preparation method, as well as a flexible OLED display. The method includes: emulsion copolymerization to form a polyacrylate copolymer containing fluorine, double bonds, silane, and hydroxyl functional monomers; chemically bonding KH-570 modified nano-silica material into a polymer network using in-situ polymerization to prepare a composite emulsion; finally, forming an organic encapsulation layer through slot coating combined with UV-thermal dual curing, and alternately constructing alumina and alumina inorganic barrier layers using atomic layer deposition technology to form a multilayer organic-inorganic composite structure. This invention, through the synergy of molecular design, nanocomposite technology, and multilayer construction, enables the encapsulation material to possess ultra-low water vapor permeability (<10). ‑6 g / m 2 With its high flexibility, strong interface adhesion, and excellent thermal stability, it effectively solves the water and oxygen sensitivity problem of flexible OLED components and is suitable for packaging high-end flexible display devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flexible OLED display packaging technology, specifically relating to a multilayer composite packaging material and its preparation method, and a flexible OLED display. Background Technology

[0002] Flexible organic light-emitting diodes (OLEDs), with their unique advantages such as self-emission, wide viewing angle, high contrast, fast response speed, and the ability to achieve flexible displays, have become the core of next-generation display and lighting technologies. With the rise of new electronic products such as foldable phones, wearable devices, and rollable TVs, the demand for flexible OLED displays is increasingly urgent. However, the commercial application of flexible OLED displays has always faced a key bottleneck: the highly sensitive organic light-emitting materials and metal electrodes inside are extremely susceptible to corrosion by moisture and oxygen in the environment. Water and oxygen penetration can trigger a series of problems such as photo-oxidation of organic materials, electrode corrosion, and interface degradation, leading to dark spots, black patches, and a sharp drop in brightness, ultimately causing rapid performance degradation and the end of the device's lifespan.

[0003] To achieve flexibility, traditional rigid glass or metal cover encapsulation methods must be abandoned in favor of thin-film encapsulation technology. This technology forms a physical barrier by constructing ultra-thin, multi-layered films on the device surface. The current mainstream solution is to construct a "sandwich" structure with alternating inorganic and organic layers. The inorganic layers (such as alumina and silicon nitride), prepared using atomic layer deposition or chemical vapor deposition, possess atomic-level density and act as the primary barrier against water and oxygen permeation. However, when pure inorganic films are mechanically bent or stretched, internal stress can easily lead to the generation and propagation of microcracks, creating rapid channels for water and oxygen permeation. The organic polymer layers (such as acrylates and epoxy resins) play a dual role: on the one hand, their flexibility can buffer stress, inhibit the propagation of cracks in the inorganic layer, and cover potential pinhole defects in the underlying inorganic layer; on the other hand, the organic layer itself also has a certain barrier capacity and can extend the diffusion path of water and oxygen molecules.

[0004] While this alternating organic-inorganic multilayer structure has proven to be an effective flexible encapsulation strategy, existing technologies still face several challenges in practical applications. Firstly, the intrinsic water vapor permeability of most commercially available organic encapsulation materials is typically around 10%. -3 Up to 10 -5 g / m 2 • On a daily scale, it is difficult to meet the ultra-high barrier performance (WVTR < 10) requirements of OLED devices on their own. -6 g / m 2First, the organic and inorganic layers typically rely on physical adsorption or weak van der Waals forces for bonding. Under long-term thermal stress or dynamic bending conditions, the interface is prone to delamination, leading to encapsulation failure. Second, to improve the barrier properties and mechanical properties of the organic layer, inorganic nanofillers (such as silica and montmorillonite) are often introduced for composite processing. However, nanoparticles are prone to agglomeration in the polymer matrix due to their high surface energy, which not only fails to achieve effective reinforcement but may also become defect points, reducing the uniformity and density of the film. Finally, the temperature window of the encapsulation process is also limited. Excessively high processing temperatures can damage the underlying OLED functional layer, while excessively low temperatures may lead to insufficient cross-linking of the organic layer or insufficient density of the inorganic layer.

[0005] Therefore, developing a novel encapsulation material system and integration process requires systematic innovation across three dimensions: molecular structure design, nanocomposite interface regulation, and multilayer structure synergy. Specifically, it necessitates designing and synthesizing a functional polymer that possesses excellent hydrophobicity, good thermal stability, strong adhesion to various substrates, and low-temperature curing capability. It also requires achieving uniform and stable dispersion of inorganic nanofillers within the polymer matrix, forming strong interfaces through chemical bonding to simultaneously enhance mechanical strength and barrier properties. Finally, it requires optimizing the preparation and integration processes of the organic and inorganic layers to ensure the formation of a defect-free, strongly bonded, dense film under low-temperature conditions, ultimately achieving ultra-low water and oxygen permeability and superior mechanical reliability that surpasses current technological levels. Summary of the Invention

[0006] The purpose of this invention is to address the technical bottlenecks in existing flexible OLED thin-film encapsulation technologies, such as insufficient intrinsic barrier properties of the organic layer, weak organic / inorganic interfacial bonding, susceptibility to microcracks in the inorganic layer, and device damage during high-temperature processes. This invention provides a synergistic solution from molecular design and nanocomposite construction to multilayer construction. Specifically, this invention aims to provide a multilayer composite encapsulation material and its preparation method. This method utilizes ingenious functional monomer copolymerization design to construct a polymer matrix possessing high hydrophobicity, good thermal stability, and strong interfacial reactivity. In-situ polymerization achieves chemical bonding between nanoparticles and the polymer network, significantly improving the density and mechanical properties of the organic layer. Finally, a low-temperature, mild slot coating and atomic layer deposition process is employed to construct a multilayer organic-inorganic alternating "sandwich" composite structure, synergistically achieving ultra-high water and oxygen barrier properties, excellent flexibility, and reliable interfacial bonding to meet the long lifespan requirements of high-end flexible OLED displays.

[0007] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows: A method for preparing a multilayer composite encapsulation material includes the following steps: Step 1: Synthesis of functionalized polyacrylate copolymer emulsion.

[0008] Functionalized polyacrylate copolymer emulsions were prepared by emulsion copolymerization using butyl acrylate and methyl methacrylate as main monomers and introducing trifluoroethyl methacrylate, allyl methacrylate, propyl 3-trimethoxysilane acrylate and hydroxyethyl methacrylate as functional monomers. The core of this step lies in synthesizing a multifunctional polymer matrix through molecular design. Butyl acrylate and methyl methacrylate are used as the main monomers. Butyl acrylate provides flexibility and good film-forming properties, while methyl methacrylate imparts rigidity and heat resistance to the polymer. Four functional monomers are synergistically introduced: trifluoroethyl methacrylate, whose fluorine atoms in the molecular chain have extremely low surface energy, significantly reducing the surface tension of the polymer and endowing the material with excellent hydrophobicity and chemical inertness, thus improving barrier properties from the source; allyl methacrylate, providing sites for subsequent grafting reactions; propyl 3-trimethoxysilane acrylate, whose terminal methoxysilyl group can undergo subsequent hydrolysis and condensation, forming interfacial chemical coupling with the subsequently atomically deposited alumina inorganic barrier layer (Al2O3), greatly enhancing interlayer adhesion; and hydroxyethyl methacrylate, whose side chain hydroxyl groups improve emulsion stability and act as crosslinking points in subsequent UV or thermosetting reactions, increasing the crosslinking density and solvent resistance of the polymer network. The functionalized polyacrylate copolymer emulsion is prepared by emulsion copolymerization under mild conditions (e.g., 60-80℃) in the presence of an initiator (such as ammonium persulfate) and an emulsifier (such as sodium dodecyl sulfate). This method is mature, easy to scale up, and produces emulsions with uniform particle size and good stability.

[0009] Step 2: Preparation of composite emulsion.

[0010] The surface of nano-silica material was modified using silane coupling agent KH-570 to introduce polymerizable double bonds on the surface of the nano-silica material. The modified nano-silica material was dispersed in a functionalized polyacrylate copolymer emulsion and butyl acrylate was added. Under the action of an initiator, the polymerizable double bonds on the surface of the nano-silica material participated in the copolymerization reaction to obtain a composite emulsion. To further enhance the density and mechanical strength of the organic encapsulation layer, this step introduces nano-silica material for composite reinforcement. First, the nano-silica material is surface-modified using the silane coupling agent KH-570. The trimethoxysilane group at one end of the KH-570 molecule can undergo a hydrolytic condensation reaction with the silanol groups on the surface of the nano-silica material, forming strong Si-O-Si chemical bonds. This modification process fundamentally changes the surface properties of the nano-silica material, transforming it from hydrophilic to hydrophobic and oleophilic, and giving it better compatibility with the functionalized polyacrylate copolymer emulsion. Subsequently, the surface-modified nano-silica material is uniformly dispersed in the copolymer emulsion prepared in step one. Through in-situ polymerization, the double bonds on its surface are copolymerized with the reactive bonds in the functionalized polyacrylate copolymer emulsion (including the allyl double bonds on the allyl methacrylate side chain). In step two, butyl acrylate plays a crucial role through a triple synergistic mechanism: as a comonomer, it reacts with the double bonds on the surface of KH-570-modified SiO2 to achieve in-situ chemical bonding between the inorganic core and the organic shell; as a soft monomer, it significantly lowers the glass transition temperature (Tg) of the system, enhancing film flexibility and crack resistance; and as a compatibilizer, it improves the dispersion stability of nanoparticles in the emulsion through hydrophobic matching, forming a uniform core-shell structure and maintaining the rheological properties of the system, laying the structural foundation for the subsequent uniform deposition of the ALD-alumina inorganic barrier layer. This means that the nano-silica material is not physically blended, but rather "anchored" to the crosslinking points of the polymer network through chemical bonds (CC bonds), achieving molecular-level dispersion and strong interfacial bonding of inorganic nanoparticles in the organic matrix. This chemical bonding method effectively prevents the aggregation of nanoparticles, fully utilizes their nano-effects, significantly improves the mechanical modulus and crack propagation resistance of the composite material, and further extends the diffusion path of water vapor due to its "maze effect," thus enhancing the barrier performance.

[0011] Step 3: Construction of a multi-layer organic-inorganic composite encapsulation layer.

[0012] A photoinitiator is added to the composite emulsion and coated onto the surface of a flexible substrate using a slot coating method. The substrate is then cured under ultraviolet light and subjected to heat treatment to form an organic encapsulation layer. Subsequently, an alumina inorganic barrier layer is deposited on the surface of the organic encapsulation layer using atomic layer deposition. The steps of forming the organic encapsulation layer and depositing the alumina inorganic barrier layer are repeated several times to form a multilayer composite encapsulation material.

[0013] This step aims to construct a multilayer barrier structure from the aforementioned high-performance nanocomposite emulsion using a low-temperature, precise film-forming process.

[0014] (1) Formation of the organic encapsulation layer: The nanocomposite emulsion obtained in step two is mixed with 1% 2-hydroxy-2-methyl-1-phenylpropanone as a photoinitiator, and then coated onto the surface of a flexible substrate (such as polyimide PI) in a high-precision and continuous manner using a slot coating process. Slot coating can precisely control the thickness and uniformity of the wet film. After coating, UV curing is performed first. UV curing utilizes the photoinitiator to rapidly generate free radicals under UV irradiation, which initiates the cross-linking reaction of unsaturated double bonds in the polymer, allowing the coating to quickly set within seconds, preventing flow, and forming a preliminary network structure. Subsequent heat treatment serves multiple purposes: firstly, it promotes the evaporation of residual solvents, resulting in a denser film; secondly, it induces the hydrolysis of methoxy groups in the 3-(trimethoxysilyl)propyl acrylate units to generate silanol groups, which then undergo a condensation reaction to form a Si-O-Si crosslinked network. Simultaneously, this network forms chemical bonds with the substrate, significantly enhancing the coating's cohesive strength and interfacial adhesion. Furthermore, heat treatment facilitates the further relaxation and alignment of polymer chains, eliminating internal stress. This results in a dense, tough, and highly adhesive organic encapsulation layer.

[0015] (2) Deposition of the inorganic barrier layer: On the surface of the cured organic encapsulation layer, atomic layer deposition (ALD) technology is used to alternately introduce a precursor made of trimethylaluminum and water under low-temperature conditions (e.g., 60-90℃). ALD technology is based on self-limiting surface chemical reactions. The precursor is introduced into the reaction chamber in a pulsed manner. Each reaction only adsorbs a single atomic layer on the substrate surface and reacts. This cycle is repeated, which can precisely control the film thickness to the angstrom level and achieve excellent step coverage and three-dimensional conformal properties. Even in the small undulations on the surface of the organic encapsulation layer, a uniform, dense, and pinhole-free alumina film can be deposited. This low-temperature process perfectly avoids the damage of high temperature to the underlying sensitive OLED organic functional layer.

[0016] (3) Construction of multi-layer structure: Repeat steps (1) and (2) above, alternately constructing organic encapsulation layer and alumina inorganic barrier layer. The design concept of this "sandwich" structure is that: the organic encapsulation layer, as a stress buffer layer, can cover the microscopic defects that may exist in the underlying alumina inorganic barrier layer, and release the stress generated by the difference in thermal expansion coefficients of the multi-layer film, preventing crack generation and propagation; while the newly deposited alumina inorganic barrier layer provides a new, dense atomic-level barrier. The multi-layer alternating structure makes the permeation path of water vapor and oxygen extremely tortuous. Any defect that penetrates the upper layer will be blocked by the lower organic encapsulation layer or blocked again by the next lower alumina inorganic barrier layer, thereby synergistically achieving ultra-high overall barrier performance.

[0017] Preferably, in step one, the mass ratio of the main monomer butyl acrylate to methyl methacrylate is (40-60):(30-50). This ratio range can effectively balance the flexibility and rigidity of the polymer, obtaining a matrix resin with both good film-forming properties and moderate mechanical strength.

[0018] Preferably, in step one, the total amount of the functional monomers trifluoroethyl methacrylate, allyl methacrylate, propyl 3-trimethoxysilane acrylate, and hydroxyethyl methacrylate accounts for 5%-20% of the total mass of the monomers, and the mass ratio of trifluoroethyl methacrylate, allyl methacrylate, propyl 3-trimethoxysilane acrylate, and hydroxyethyl methacrylate is 5-5-8:5:3-5:2. This amount allows for the full introduction of hydrophobic fluorine atoms, subsequent reaction double bonds, reactive silane groups, and crosslinking hydroxyl groups without significantly affecting the main chain performance, thus achieving a balance between functionality and cost.

[0019] Preferably, in step two, the nano-silica material is at least one of nano-SiO2 and nano-SiO2 composite particles; the average particle size of the nano-SiO2 is 40-60 nm. The preparation method of the nano-SiO2 composite particles includes the following steps: dispersing SiO2 particles with an average particle size of 40-60 nm in a mixed solvent of anhydrous ethanol and deionized water, adding ammonia water to adjust the pH to 8.5-9.5, and sonicating; then, under nitrogen protection, slowly adding an ethanol solution of tetraethyl orthosilicate while stirring, and continuing to stir the reaction for 3-6 hours after the addition is complete, aging after the reaction is completed, followed by centrifugation, washing, and drying to obtain the nano-SiO2 composite particles.

[0020] This invention utilizes a sol-gel method to prepare nano-SiO2 composite particles by in-situ generating small-diameter SiO2 particles on the surface of large-diameter nano-SiO2. The nanoscale protrusions on the surface of these nano-SiO2 composite particles, after being dispersed in a polyacrylate matrix, can forcibly extend the diffusion paths of small molecules such as water vapor and oxygen, forming a "maze effect." This significantly reduces the water and air permeability of the organic encapsulation layer, further overcoming the shortcomings of insufficient intrinsic barrier properties in traditional organic encapsulation layers. Furthermore, the multi-level structure of the nano-SiO2 composite particles can better enhance the modulus and toughness of the organic encapsulation layer, enabling it to better buffer the stress generated during bending of the flexible substrate. This prevents stress concentration from being transferred to the brittle alumina inorganic barrier layer, thereby reducing or delaying the initiation and propagation of microcracks in the alumina inorganic barrier layer and ensuring the long-term barrier reliability of OLED devices under dynamic bending.

[0021] Preferably, in step two, the amount of the nano-silica material used is 5%-20% of the polymer solid mass. This range of dosage ensures that the nanoparticles achieve effective reinforcement and barrier effects in the matrix, while avoiding excessive dosage that could lead to a sharp increase in emulsion viscosity, difficulty in dispersion, or a decrease in film transparency.

[0022] The amount of butyl acrylate used is 0.8%-1.3% of the solid mass of the functionalized polyacrylate copolymer emulsion obtained in step 1. Butyl acrylate plays a key role through a triple synergistic mechanism: as a comonomer, it reacts with the double bonds on the surface of KH-570-modified SiO2 to achieve in-situ chemical bonding between the inorganic core and organic shell; as a soft monomer, it significantly reduces the glass transition temperature (Tg) of the system, enhancing film flexibility and crack resistance; and as a compatibilizer, it improves the dispersion stability of nanoparticles in the emulsion through hydrophobic matching, forming a uniform core-shell structure and maintaining the rheological properties of the system, laying the structural foundation for the subsequent uniform deposition of the ALD-Al2O3 layer.

[0023] Preferably, in step three, the surface modification reaction is carried out in a mixed solvent of ethanol and water at a reaction temperature of 70-78°C for 3-6 hours. The in-situ polymerization reaction is carried out at a temperature of 65-75℃ for 1.5-3 hours.

[0024] Preferably, in step three, the UV curing light intensity is 50-100 mW / cm². 2 The wavelength is 365nm, the irradiation time is 10-60 seconds; the heat treatment temperature is 80-120℃, and the time is 20-60 minutes.

[0025] Preferably, in step three, the thickness of the organic encapsulation layer is 1-10 μm, and the thickness of the inorganic alumina barrier layer is 10-50 nm. If the organic encapsulation layer is too thin, its stress buffering and defect filling capabilities will be insufficient; if it is too thick, it will affect the overall thickness and flexibility of the device. The inorganic alumina barrier layer, within this nanometer thickness range, can ensure both density and defect-free properties while also possessing good flexibility, avoiding brittleness caused by excessive thickness.

[0026] Preferably, in step three, the total number of layers in the multi-layered alternating structure is 2-10 layers, that is, repeating steps 1-9 times to form the organic encapsulation layer and deposit the inorganic alumina barrier layer. Too few layers may not effectively block water and oxygen, while too many layers will increase process complexity and cost; this range represents the optimal balance between performance and efficiency.

[0027] Preferably, in step three, the atomic layer deposition process temperature is 60-90°C. This low temperature range is sufficient to ensure that the ALD precursor reacts fully to form a high-quality Al2O3 film, while being far below the glass transition temperature or decomposition temperature of the OLED functional layer material, thus ensuring the safety of the process.

[0028] This invention also provides a multilayer composite encapsulation material prepared by the above-described method. The water vapor transmission rate of the multilayer composite encapsulation material is less than 1.0 × 10⁻⁶. -6 g / m 2 ·day.

[0029] The present invention also provides a flexible OLED display screen, wherein the multilayer composite encapsulation material prepared by the above preparation method is used as the encapsulation layer.

[0030] Compared with the prior art, the present invention has the following significant advantages: 1. Scientific molecular structure design enhances performance: By precisely introducing fluorinated monomers and silane coupling monomers through copolymerization, the polymer simultaneously possesses low surface energy hydrophobic properties and the ability to chemically bond with inorganic interfaces. This not only improves the barrier properties from the material's intrinsic nature but also fundamentally solves the key problem of easy delamination at organic / inorganic interfaces through chemical bonding, thereby enhancing the long-term reliability of the encapsulation structure.

[0031] 2. Strong Nanocomposite Interface and Significant Reinforcing Effect: KH-570 is used to modify the surface of nano-silica materials, and chemical bonding is achieved through in-situ polymerization. This strategy completely solves the common industry problem of easy agglomeration and weak interfaces of nanofillers in polymer matrices. Chemically anchored nanoparticles act as reinforcing points, significantly improving the mechanical strength, modulus, and creep resistance of the composite material. The uniformly dispersed "nanomania" structure effectively extends and hinders the diffusion path of water vapor molecules, resulting in a synergistic enhancement of barrier properties.

[0032] 3. Low-temperature and efficient fabrication process with good compatibility: The entire process chain, from emulsion polymerization and slot coating to atomic layer deposition, can be completed at relatively low temperatures (not exceeding 90°C), making it fully compatible with temperature-sensitive flexible OLED devices. The UV-thermal dual curing strategy balances production efficiency and the full development of material properties; both slot coating and ALD technologies are suitable for large-area, roll-to-roll production, and have good industrialization prospects.

[0033] 4. Synergistic Multi-Layer Structure for Superior Overall Performance: The final organic-inorganic alternating multi-layer "sandwich" structure fully leverages the stress buffering and defect repair functions of the organic encapsulation layer and the dense barrier advantages of the alumina inorganic barrier layer. These complementary strengths work synergistically, enabling the encapsulation material to maintain high light transmittance, excellent flexibility (withstanding tens of thousands of bends), and thermal stability while achieving a water vapor transmission rate of less than 1.0 × 10⁻⁶. -6 g / m 2 The ultra-high barrier grade of ·day can meet the most stringent requirements for encapsulation life of flexible OLED display devices. Attached Figure Description

[0034] Figure 1 This is a flowchart illustrating the steps of a polymer encapsulation material preparation process for OLED flexible components provided in an embodiment of the present invention. Detailed Implementation

[0035] To make the technical solution and advantages of this invention clearer and more complete, the implementation process of this invention will be described in detail below with reference to specific embodiments, and comparative experiments will be provided to demonstrate the effectiveness of this invention. It should be understood that the embodiments described herein are only for explaining this invention and are not intended to limit the scope of protection of this invention. Equivalent changes or modifications made to the steps, conditions, parameters, etc., of this invention without departing from the spirit and substance of this invention should be included within the scope of protection of this invention.

[0036] Example 1:

[0037] 1. Synthesis of Functionalized Polyacrylate Copolymer Emulsions In a 1000 mL four-necked flask, assemble a mechanical stirrer, reflux condenser, constant pressure dropping funnel, and nitrogen inlet tube. Add 200 g of deionized water and 2.0 g of sodium dodecyl sulfate (emulsifier) ​​sequentially, and start stirring to dissolve. While stirring, slowly add the following monomers in sequence: 50.0 g of butyl acrylate, 35.0 g of methyl methacrylate, 5.0 g of trifluoroethyl methacrylate, 5.0 g of allyl methacrylate, 3.0 g of propyl 3-trimethoxysilane acrylate, and 2.0 g of hydroxyethyl methacrylate. The total mass of monomers is 100.0 g. Continue stirring for 30 minutes to form a homogeneous pre-emulsion.

[0038] High-purity nitrogen gas was introduced into the system for 30 minutes to fully replace the air. The water bath was heated to 75°C and kept stable. Under continuous nitrogen purging, 0.5 g of potassium persulfate initiator solution dissolved in 10 g of deionized water was slowly added dropwise over 30 minutes using a dropping funnel. After the addition was complete, the reaction was maintained at 75°C for 6 hours. The reaction system gradually changed from milky white to a bluish-green translucent emulsion, indicating the formation of stable polymer latex particles. After the reaction was completed, the system was cooled to room temperature, and the pH of the emulsion was adjusted to 7-8 with a 10% ammonia solution. Then, it was filtered through a 400-mesh nylon filter cloth to obtain the functionalized polyacrylate copolymer emulsion, labeled as Emulsion A.

[0039] 2. Preparation of nano-SiO2 / polymer composite emulsion Surface modification of nano-SiO2: 10.0 g of nano-SiO2 with an average particle size of 52 nm was weighed and dispersed in a mixed solution of 95 mL anhydrous ethanol and 5 mL deionized water. The solution was sonicated for 30 minutes. The dispersion was transferred to a 250 mL three-necked flask, and 1.2 g of silane coupling agent KH-570 (γ-methacryloyloxypropyltrimethoxysilane) was added. A small amount of glacial acetic acid was added to adjust the pH of the system to 3.5-4.0. The mixture was stirred at 75 °C for 4 hours. After the reaction was completed, the mixture was centrifuged (8000 rpm, 10 minutes), the supernatant was discarded, and the precipitate was washed three times with anhydrous ethanol. The precipitate was then vacuum dried at 80 °C for 12 hours to obtain surface-modified nano-SiO2.

[0040] In-situ polymerization preparation of composite emulsion: The surface-modified nano-SiO2 was redispersed in 50 g of deionized water and sonicated in an ice-water bath for 1 hour to obtain a uniform dispersion. This dispersion was slowly added dropwise to 250 g (approximately 100 g of solids) of emulsion A under high-speed stirring (1000 rpm). After the addition was complete, 1% (relative to the mass of polymer solids in emulsion A) of butyl acrylate and 0.1 g of ammonium persulfate initiator were added, and the reaction was continued at 70°C under nitrogen protection for 2 hours with stirring. After the reaction was completed, a uniform and stable composite emulsion was obtained, labeled as emulsion B.

[0041] 3. Construction of multilayer organic-inorganic composite encapsulation layers Substrate preparation: A 125 μm thick polyimide film was used as the flexible substrate. The sample was ultrasonically cleaned with acetone, ethanol, and deionized water for 10 minutes each, dried with nitrogen, and then dried in an 80°C oven for 30 minutes before use.

[0042] Organic encapsulation layer coating and curing: Emulsion B was mixed with 1% 2-hydroxy-2-methyl-1-phenylpropanone as a photoinitiator and then filtered through a 200-mesh stainless steel screen. A slot coater was used with a coating speed of 5 mm / s and a slot gap of 50 μm to coat the clean polyimide substrate, achieving a wet film thickness of approximately 20 μm. Immediately after coating, an 80 mW / cm² coating was applied. 2 The sample was cured by irradiation with a UV lamp (main wavelength 365 nm) for 30 seconds. Then, the sample was placed in a 100°C forced-air oven for 30 minutes to form the first organic encapsulation layer (dry film thickness of about 5 μm).

[0043] Alumina inorganic barrier layer deposition: The sample obtained through the above steps was placed in the reaction chamber of an atomic layer deposition (ALD) apparatus, and the temperature was set to 85°C. Trimethylaluminum and deionized water were used as precursors, and nitrogen was used as the carrier gas. Each deposition cycle consisted of: a 0.1-second TMA pulse → a 10-second nitrogen purging → a 0.1-second H₂O pulse → a 10-second nitrogen purging. This process was repeated 200 times to deposit an approximately 20 nm thick alumina inorganic barrier layer on the surface of the organic encapsulation layer.

[0044] Multilayer structure construction: Repeat the above organic encapsulation layer coating and curing-alumina inorganic barrier layer deposition process to finally obtain a four-layer composite encapsulation material of "organic encapsulation layer (5 μm) / alumina inorganic barrier layer (20 nm) / organic encapsulation layer (5 μm) / alumina inorganic barrier layer (20 nm)".

[0045] Example 2:

[0046] The only difference between this embodiment and Embodiment 1 is the following parameters: Step 1 Monomer ratio: Increase trifluoroethyl methacrylate to 8.0 g, increase propyl 3-trimethoxysilane acrylate to 5.0 g, keep allyl methacrylate at 5.0 g, keep hydroxyethyl methacrylate at 2.0 g, reduce methyl methacrylate to 30.0 g, and keep butyl acrylate at 50.0 g.

[0047] Step 2: Nanofiller: The amount of nano-SiO2 is increased to 15.0 g.

[0048] Step 3: Alumina inorganic barrier layer: The number of ALD deposition cycles is increased to 300 (the alumina inorganic barrier layer is about 30nm thick).

[0049] The remaining steps and conditions are exactly the same as in Example 1.

[0050] Example 3:

[0051] The only difference between this embodiment and Embodiment 1 is the number of layers in the composite encapsulation material: After completing the first "organic encapsulation layer / alumina inorganic barrier layer" construction, the second organic encapsulation layer is coated and cured, followed by the second alumina inorganic barrier layer deposition. Then, the third organic encapsulation layer coating and curing, and the third alumina inorganic barrier layer deposition are performed. The final structure is: polyimide substrate / organic encapsulation layer / alumina inorganic barrier layer / organic encapsulation layer / alumina inorganic barrier layer / organic encapsulation layer / alumina inorganic barrier layer (a total of six layers).

[0052] All other parameters are the same as in Example 1.

[0053] Example 4:

[0054] The only difference between this embodiment and Embodiment 1 is the heat treatment conditions for the organic encapsulation layer in step 3: The heat treatment temperature is 120℃ for 20 minutes. This promotes more complete hydrolysis and condensation of silanoxy groups and densification of polymer chains.

[0055] All other steps and parameters are the same as in Example 1.

[0056] Example 5:

[0057] The only difference between this embodiment and Embodiment 1 is that the nano-SiO2 with an average particle size of 52 nm is replaced with nano-SiO2 composite particles. The preparation method of the nano-SiO2 composite particles includes the following steps: The preparation of nano-SiO2 composite particles can be achieved by in-situ generation of small-sized SiO2 particles on the surface of large-sized SiO2 particles via the sol-gel method. The specific process is as follows: 10.0 g of SiO2 particles with an average particle size of 52 nm are weighed and dispersed in a mixed solvent of 90 mL anhydrous ethanol and 10 mL deionized water. Ammonia is added to adjust the pH to 9.0, and the mixture is sonicated for 30 minutes to ensure uniform dispersion and prevent agglomeration. The dispersion is transferred to a 250 mL three-necked flask, protected with nitrogen gas, and 2.0 g of a tetraethyl orthosilicate (TEOS) ethanol solution (TEOS:EtOH = 1:4 v / v) is slowly added dropwise over 30 minutes with stirring. After the addition is complete, the reaction continues for 4 hours. Vigorous stirring is avoided during the reaction to prevent the shedding of newly formed particles or the formation of free small particles through homogeneous nucleation. After the reaction is complete, the mixture is aged for another 6 hours, followed by centrifugation (8000 rpm). (10 minutes at rpm), discard the supernatant, wash the precipitate three times with anhydrous ethanol to remove unreacted substances and byproducts; finally, vacuum dry the precipitate at 80℃ for 12 hours to obtain nano-SiO2 composite particles.

[0058] All other steps and parameters are the same as in Example 1.

[0059] Comparative Example 1: Single Organic Encapsulation Layer (Comparison) A commercially available, standard flexible UV-curable acrylic encapsulant (fluorine-free, silane-free, and nanofiller-free) was used. It was slit-coated onto a similarly treated polyimide substrate, with a wet film thickness of approximately 80 μm, and subjected to a curing temperature of 80 mW / cm². 2 Complete curing is achieved by irradiation with ultraviolet light (365 nm) for 60 seconds, forming a single organic encapsulation layer (dry film thickness approximately 40 μm). No heat treatment or alumina inorganic barrier layer deposition is performed.

[0060] Comparative Example 2: Single Inorganic Encapsulation Layer (Comparison) Four layers of inorganic aluminum oxide thin films (each layer 20 nm thick, total thickness 80 nm) were directly deposited on a polyimide substrate using atomic layer deposition technology, without preparing any organic encapsulation layer.

[0061] Comparative Example 3: Unmodified nanoparticle physical blend + single-layer alumina inorganic barrier layer (comparison) Unlike Example 1, untreated nano-SO2 with an average particle size of 52 nm was physically blended into a common acrylate emulsion to prepare an organic encapsulation layer. Then, a 20 nm alumina inorganic film was deposited to form a bilayer structure of "organic encapsulation layer / alumina inorganic barrier layer".

[0062] All other steps and parameters are the same as in Example 1.

[0063] Comparative Example 4: Composite Encapsulation Materials with Fluorine-Free and Silane-Free Functional Monomers (Comparison) Unlike Example 1, when synthesizing the polyacrylate emulsion, only butyl acrylate, methyl methacrylate and allyl methacrylate were used as monomers, and trifluoroethyl methacrylate and propyl 3-trimethoxysilane acrylate were omitted. The rest of the preparation process and multilayer structure were exactly the same as in Example 1.

[0064] All other steps and parameters are the same as in Example 1.

[0065] Comparative Example 5: Unlike Example 1, no surface modification was performed on the nano-SiO2.

[0066] The preparation method of the composite emulsion includes the following steps: 10.0 g of nano-SiO2 with an average particle size of 52 nm was weighed and dispersed in 50 g of deionized water. The dispersion was ultrasonically treated in an ice-water bath for 1 hour to obtain a homogeneous dispersion. This dispersion was slowly added dropwise to 250 g (approximately 100 g of solids) of emulsion A under high-speed stirring (1000 rpm). After the addition was complete, 1% (relative to the mass of polymer solids in emulsion A) of butyl acrylate was added, along with 0.1 g of ammonium persulfate initiator. The reaction was continued at 70 °C under nitrogen protection for 2 hours with stirring. After the reaction was complete, a homogeneous and stable composite emulsion was obtained, labeled as emulsion B.

[0067] All other steps and parameters are the same as in Example 1.

[0068] Comparative Example 6: Unlike Example 1, no additional butyl acrylate was added.

[0069] The preparation method of the composite emulsion includes the following steps: Surface modification of nano-SiO2: 10.0 g of nano-SiO2 with an average particle size of 52 nm was weighed and dispersed in a mixed solution of 95 mL anhydrous ethanol and 5 mL deionized water. The solution was sonicated for 30 minutes. The dispersion was transferred to a 250 mL three-necked flask, and 1.2 g of silane coupling agent KH-570 (γ-methacryloyloxypropyltrimethoxysilane) was added. A small amount of glacial acetic acid was added to adjust the pH of the system to 3.5-4.0. The mixture was stirred at 75 °C for 4 hours. After the reaction was completed, the mixture was centrifuged (8000 rpm, 10 minutes), the supernatant was discarded, and the precipitate was washed three times with anhydrous ethanol. The precipitate was then vacuum dried at 80 °C for 12 hours to obtain surface-modified nano-SiO2.

[0070] In-situ polymerization preparation of composite emulsion: The surface-modified nano-SiO2 was redispersed in 50 g of deionized water and sonicated in an ice-water bath for 1 hour to obtain a uniform dispersion. This dispersion was slowly added dropwise to 250 g (approximately 100 g of solids) of emulsion A under high-speed stirring (1000 rpm). After the addition was complete, 0.1 g of ammonium persulfate initiator was added, and the reaction was continued at 70°C under nitrogen protection for 2 hours. After the reaction was completed, a uniform and stable composite emulsion was obtained, labeled as emulsion B.

[0071] All other steps and parameters are the same as in Example 1.

[0072] Performance Testing and Result Analysis The encapsulated samples prepared in Examples 1-5 and Comparative Examples 1-6 were subjected to system performance tests. The test methods and results are as follows.

[0073] I. Testing Methods 1. Water vapor transmission rate (WVTR): A dedicated high-barrier testing system based on the calcium corrosion testing principle was used. The testing conditions were 38℃ and 90% relative humidity (RH). This method can accurately measure water vapor transmission rate as low as 10. -7 g / m 2 • Daily water vapor infiltration rate.

[0074] 2. Adhesion: Refer to GB / T 9286-1998 standard, use a cross-cutting tool to make a 1mm×1mm grid on the coating surface, and use 3M 600 tape to perform a peel test. The grade is rated according to the area of ​​coating peeling (0 is the best, 5 is the worst).

[0075] 3. Transmittance: The transmittance of the packaged sample was measured at a wavelength of 550 nm using a UV-Vis spectrophotometer to evaluate its impact on the luminous efficiency of the display device.

[0076] 4. Bending performance: Using a programmable bending tester, the sample was repeatedly bent around a cylinder with a radius of 3 mm at a bending angle of 180° and a frequency of 1 Hz. The appearance changes (such as cracks) of the sample after 100,000 bends were recorded, and the change in WVTR after bending was tested.

[0077] 5. Environmental Reliability: The samples were placed in a high-temperature and high-humidity aging chamber at 85℃ and 85%RH for 1000 hours. The change rate of WVTR before and after aging was tested to evaluate the long-term stability of the packaging structure.

[0078] II. Summary Table of Test Results III. Results Analysis and Discussion 1. Achievement of ultra-low water vapor transmission rate: The WVTR of Examples 1-5 is consistently maintained at 10. -7 g / m 2 • Day-level, as low as 3.1 × 10 -7 It is far superior to the 10 compared to proportions 1-6. -6 Up to 10 -2 The core of this level lies in the labyrinthine barrier pathway constructed by alternating organic and inorganic layers. The inorganic layer provides an atomically dense barrier, while the organic layer reduces the surface energy to <20 mN / m through fluoroalkyl hydrophobic groups (trifluoroethyl methacrylate), effectively inhibiting water molecule adsorption and capillary permeation. Simultaneously, the KH-570-mediated Si-OC covalent network eliminates interfacial microporous channels, resulting in multiple blockages of water vapor diffusion pathways. In contrast, the single organic layer in Comparative Example 1, lacking crosslinking and hydrophobic groups, exhibits a WVTR as high as 1.5 × 10⁻⁶. -2Although the pure inorganic layer in Comparative Example 2 was dense, its brittle cracking led to the permeation channels being connected. In Comparative Example 3, the brittleness was due to the lack of bonding of fillers, the absence of fluorine hydrophobicity, or interface debonding, and none of these conditions could form a continuous and dense barrier structure.

[0079] 2. Effect of number of layers on barrier performance: WVTR (3.1 × 10⁻⁶) of Example 3 (six-layer structure) -7 (Lower than Example 1 (four layers, 8.5 × 10)) -7 Example 2 (four layers but thickened, 5.2 × 10⁻⁶) is similar to Example 3 (four layers but thickened, 5.2 × 10⁻⁶). -7 The results indicate that increasing the number of alternating organic and inorganic layers significantly improves barrier efficiency. Each additional layer introduces stress buffering and crack deflection mechanisms, forcing water vapor to traverse more tortuous paths. Furthermore, the multilayer structure reduces overall internal stress accumulation through "interlayer stress cancellation," preventing brittle failure caused by excessively thick single layers. In contrast, the single-layer 80 nm Al2O3 in Comparative Example 2, lacking organic layer buffering, developed through-cracks during bending, causing its WVTR to surge to 2.1 × 10⁻⁶. -6 This proves that the number of layers is not a simple superposition, but rather a nonlinear leap in barrier performance achieved through structural design.

[0080] 3. The crucial role of chemical bonding: In Examples 1-5, the molecular-level covalent bonding between the inorganic filler and the organic matrix is ​​achieved through the bifunctional groups of KH-570, forming a Si-O-Si (inorganic) and CC (organic) cross-phase network with an interfacial binding energy >150 J / m. 2 Far exceeding the <10 J / m³ of physical adsorption 2 Comparative Example 5, although butyl acrylate was added, did not use KH-570 to modify SiO2, resulting in SiO2 only being physically adsorbed onto the polymer surface. After bending, the interfacial peeling area reached 80%, and the WVTR increased to 1.2 × 10⁻⁶. -5 In Comparative Example 6, omitting the addition of butyl acrylate resulted in a significant decrease in the degree of free radical copolymerization, demonstrating that butyl acrylate plays a key role through multiple synergistic mechanisms, which is the molecular basis for achieving high-reliability encapsulation.

[0081] 4. Excellent mechanical properties and interface reliability: Examples 1-5 showed no cracks in 100,000 bending radius tests with a 3 mm radius, achieving an adhesion level of 0. In contrast, Comparative Examples 1-6 showed varying degrees of cracking or peeling. The mechanism lies in the high toughness of the organic layer (E≈1 GPa) and the high modulus of the inorganic layer (E≈200 GPa), which forms a modulus gradient buffer zone, allowing strain energy to be released gradually along the thickness direction. During crack propagation, the organic layer pins, deflects, or terminates the cracks. Furthermore, the crosslinking of fluoroalkyl and silane enhances the cohesive force within the matrix. Due to the low crosslinking density of the single organic layer in Comparative Example 1, the WVTR change rate after bending was >500%. In Comparative Example 3, stress concentration was caused by the agglomeration of unmodified SiO2, resulting in star-shaped crack propagation within the organic layer. In Comparative Examples 5 and 6, due to weak interfacial bonding, the cracks peeled off along the interface in a comb-like pattern. This demonstrates that chemical bonding and multilayer structure are dual guarantees of mechanical reliability.

[0082] 5. Excellent optical performance and environmental durability: The transmittance of Examples 1-5 is all >90%, which is far superior to that of Comparative Example 5 (89%) and Comparative Example 6 (90%). This is because the nano-SiO2 is uniformly dispersed after surface modification, without light scattering agglomeration, and the fluoroalkyl group in the organic layer reduces the refractive index fluctuation. In Comparative Example 5, the light scattering is enhanced due to the agglomeration of unmodified SiO2, resulting in a decrease in transmittance. After aging for 1000 h, the WVTR change rate of Examples 1-5 is all <12%, while that of Comparative Examples 1-6 is generally >80%, with Comparative Example 3 reaching as high as 120%. Comparative Example 4, due to the absence of fluorinated hydrophobic groups, induced internal stress by absorbing water and swelling, leading to the propagation of microcracks at the interface. This proves that the functional monomer and chemical bonding together construct the resistance to damp heat aging.

[0083] 6. The necessity of organic-inorganic composite structures: Neither a single organic layer (Comparative Example 1) nor a single inorganic layer (Comparative Example 2) can simultaneously achieve flexibility and barrier properties. The former has high permeability, while the latter is brittle and easily cracked. Examples 1-5 achieve a balance of rigidity and flexibility through alternating stacking. The organic layer absorbs strain, while the inorganic layer blocks molecular permeation. Together, they form a stress-diffusion bifunctional system. In Comparative Example 4, although the multilayer structure is retained after omitting the fluoroalkyl and silane monomers, the WVTR increases to 6.7 × 10⁻⁶. -6 The adhesion dropped to level 1, proving that the effectiveness of the composite structure depends on the chemical design of the functional monomers. The structure is the carrier, and the chemistry is the soul.

[0084] 7. Importance of Nanoparticle Modification and Dispersion: Example 5 uses nano-SiO2 composite particles (large-diameter core + small-diameter shell) grown in situ using the sol-gel method. The surface roughness and interfacial contact area are significantly improved, forming a mechanical interlocking effect with the polymer matrix, further enhancing interfacial bonding. WVTR (6.3 × 10⁻⁶) -7 The results showed that the method was superior to Example 1, while Comparative Example 5, which used unmodified SiO2 physical blending, resulted in uneven dispersion leading to agglomeration. Cracks propagated in a star-shaped pattern along the edges of the agglomerates, and the WVTR reached as high as 1.2 × 10⁻⁶.-5 This demonstrates that the surface engineering and dispersion state of nanofillers directly determine the compactness and mechanical uniformity of composite materials.

[0085] 8. Key roles of functional monomers: Trifluoroethyl methacrylate provides hydrophobicity, reducing surface energy and affinity for water molecules; propyl 3-trimethoxysilane acrylate and hydroxyethyl methacrylate synergistically enhance crosslinking density and polar anchor points; allyl methacrylate acts as a crosslinking aid to improve network stability; butyl acrylate acts as a flexible monomer to regulate the glass transition temperature. In Comparative Example 4, omitting fluorine and silane monomers, the WVTR increased to 6.7 × 10⁻⁶. -6 The adhesion decreased, and the change rate after aging reached 85%, proving that each functional monomer is indispensable. Their synergistic effect constructs a four-dimensional functional system of "hydrophobic-crosslinking-flexibility-bonding", which is the chemical cornerstone for achieving ultra-low WVTR and high reliability.

[0086] In summary, this invention, through meticulous molecular design, innovative nanocomposite strategies, and optimized multilayer construction processes, has successfully prepared an OLED flexible component encapsulation material with excellent water vapor barrier properties, strong adhesion, good flexibility, and environmental stability, solving the problem of balancing barrier properties, flexibility, and reliability in existing technologies.

Claims

1. A method for preparing a multilayer composite encapsulation material, characterized in that, Includes the following steps: Step 1: Using butyl acrylate and methyl methacrylate as the main monomers, and introducing trifluoroethyl methacrylate, allyl methacrylate, propyl 3-trimethoxysilane acrylate and hydroxyethyl methacrylate as functional monomers, functionalized polyacrylate copolymer emulsions are prepared by emulsion copolymerization. Step 2: The surface of the nano-silica material is modified with silane coupling agent KH-570 to introduce polymerizable double bonds on the surface of the nano-silica material; the modified nano-silica material is dispersed in a functionalized polyacrylate copolymer emulsion and butyl acrylate is added. Under the action of an initiator, the polymerizable double bonds on the surface of the nano-silica participate in the copolymerization reaction to obtain a composite emulsion. Step 3: Add a photoinitiator to the composite emulsion and coat it onto the surface of a flexible substrate using a slot coating method. Then, cure it with ultraviolet light and heat treatment to form an organic encapsulation layer. Subsequently, deposit an alumina inorganic barrier layer on the surface of the organic encapsulation layer using atomic layer deposition. Repeat the steps of forming the organic encapsulation layer and depositing the alumina inorganic barrier layer several times to form a multilayer composite encapsulation material.

2. The preparation method according to claim 1, characterized in that, In step 1, the mass ratio of butyl acrylate to methyl methacrylate is (40-60):(30-50); the total amount of trifluoroethyl methacrylate, allyl methacrylate, propyl 3-trimethoxysilane acrylate, and hydroxyethyl methacrylate accounts for 5%-20% of the total mass of all monomers; the mass ratio of trifluoroethyl methacrylate, allyl methacrylate, propyl 3-trimethoxysilane acrylate, and hydroxyethyl methacrylate is 5-8:5:3-5:

2.

3. The preparation method according to claim 1, characterized in that, In step 2, the nano-silica material is at least one of nano-SiO2 and nano-SiO2 composite particles; the average particle size of the nano-SiO2 is 40-60 nm. The preparation method of the nano-SiO2 composite particles includes the following steps: dispersing SiO2 particles with an average particle size of 40-60 nm in a mixed solvent of anhydrous ethanol and deionized water, adding ammonia water to adjust the pH to 8.5-9.5, and sonicating; then, under nitrogen protection, slowly adding an ethanol solution of tetraethyl orthosilicate while stirring, and continuing to stir the reaction for 3-6 hours after the addition is complete, aging after the reaction is completed, followed by centrifugation, washing, and drying to obtain the nano-SiO2 composite particles.

4. The preparation method according to claim 1, characterized in that, In step 2, the amount of the nano-silica material used is 5%-20% of the solid mass of the functionalized polyacrylate copolymer emulsion obtained in step 1; The amount of butyl acrylate used is 0.8%-1.3% of the solid mass of the functionalized polyacrylate copolymer emulsion obtained in step 1.

5. The preparation method according to claim 1, characterized in that, In step 2, the surface modification reaction is carried out in a mixed solvent of ethanol and water at a temperature of 70-78°C for 3-6 hours. The in-situ polymerization reaction is carried out at a temperature of 65-75℃ for 1.5-3 hours.

6. The preparation method according to claim 1, characterized in that, In step 3, the UV curing light intensity is 50-100 mW / cm². 2 The wavelength is 365nm, the irradiation time is 10-60 seconds; the heat treatment temperature is 80-120℃, and the time is 20-60 minutes.

7. The preparation method according to claim 1, characterized in that, In step 3, the deposition temperature of atomic layer deposition is 60-90℃, the precursors used are trimethylaluminum and water, and the single-layer thickness of the alumina inorganic barrier layer is 10-50 nm.

8. The preparation method according to claim 1, characterized in that, In step 3, the thickness of the organic encapsulation layer is 1-10 μm; the thickness of the inorganic alumina barrier layer is 10-50 nm; and the steps of forming the organic encapsulation layer and depositing the inorganic alumina barrier layer are repeated 1-9 times.

9. A multilayer composite encapsulation material, characterized in that, The multilayer composite encapsulation material prepared by the method according to any one of claims 1-8 has a water vapor permeability of less than 1.0 × 10⁻⁶. -6 g / m 2 ·day.

10. A flexible OLED display screen, characterized in that, The multilayer composite encapsulation material prepared by any one of the preparation methods according to claims 1 to 8 or the multilayer composite encapsulation material according to claim 9 is used as the encapsulation layer.